(3TQM GdeYdbGJ GdSHYs - (3GdMSjfj Hf CMeO Hf GdMSjfj GdRhRfj, CHh YHO Gddg,J (B486 (3g` s
(3ChdgG (B:s
(3bGd GdbGVi GdEeGe gPG TQM GdbUGFO GdSHY CedjJg Ydi MO GdGjLGR hGdGNJUGQ s
(3BNQgG (B:s
(3jbhd hgh Gdedc hGdTGgO Ydi MSf HdGFfG jhe bJGdfG HgPG GdehVY hGdZfG ZfGA Je GdcJGH HMeO Gddg hefg s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH GdChds
(3GdfSNI HgG MhGTs
(3bQf GdfSN (B:s
(3GdbQf GdSGOSs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B2 - (3U (B231s
(3cTa GdXfhf dMGLi NdjaI(B: (3L (B2 - (3U (B1741s
Keywords: (3GdCOHs